2020
DOI: 10.3390/nu12010260
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Daily Sodium Intake Lower than 1500 mg Is Associated with Inadequately Low Intake of Calorie, Protein, Iron, Zinc and Vitamin B1 in Patients on Chronic Hemodialysis

Abstract: Background: To measure daily sodium intake in patients on chronic hemodialysis and to compare the intake of nutrients, minerals, trace elements, and vitamins in patients who had a daily sodium intake below or above the value of 1500 mg recommended by the American Heart Association. Methods: Dietary intake was recorded for 3 days by means of 3-day diet diaries in prevalent patients on chronic hemodialysis. Each patient was instructed by a dietitian on how to fill the diary, which was subsequently signed by a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…There is an association between salt intake and nutrition intake. Bossola et al [ 10 ] showed that patients with a daily sodium intake lower than 1,500 mg, in comparison with those with an intake of 1,500 mg or more, were at a significantly greater risk of inadequate calorie and protein intakes as well as a low intake of iron and zinc. Similarly, Xie et al [ 8 ] suggested that efforts to intensify sodium restriction might increase the risk of compromising energy intake further.…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is an association between salt intake and nutrition intake. Bossola et al [ 10 ] showed that patients with a daily sodium intake lower than 1,500 mg, in comparison with those with an intake of 1,500 mg or more, were at a significantly greater risk of inadequate calorie and protein intakes as well as a low intake of iron and zinc. Similarly, Xie et al [ 8 ] suggested that efforts to intensify sodium restriction might increase the risk of compromising energy intake further.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Xie et al [ 9 ] reported that malnutrition and the risk of protein-energy wasting may occur following a sodium-restricted diet because sodium is widely used in a variety of foods. Bossola et al [ 10 ] reported that a low daily intake of sodium is associated with an inadequately low intake of calories, proteins, minerals, trace elements, and vitamin B1. Furthermore, it was suggested that a low salt intake (< 6 g/day) was associated with an increased risk for all-cause mortality and cardiovascular death, resulting in an L-shaped association curve in Japanese patients on hemodialysis [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the fact that the kidney mostly relies on lactate as the gluconeogenic substrate, and renal insufficiency could affect the systemic clearance of lactate, giving rise to hyperlactatemia ( 27 ). In addition, patients undergoing chronic hemodialysis are more likely to be deficient in thiamine due to strict dietary control, which may cause pyruvate to shift to anaerobic metabolism ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…31 Recent studies have shown that a low daily intake of sodium is associated with inadequate calories, proteins, carbohydrates, and fibre consumption, as well as with a low intake of vitamins and minerals. [23][24][25] Older patients are particularly vulnerable to low dietary sodium intake as taste perception decreases with age, causing reduced food intake. 32 Malnutrition can contribute to adipose tissue wasting and lead to the depletion of muscle mass, thereby triggering weight loss.…”
Section: Discussionmentioning
confidence: 99%